In situ adsorption densities of polyacrylates on hematite nano-particle films as determined by ATR-FTIR spectroscopy - Van Bronswijk, Wilhelm; Kirwan, Luke; Fawell, Phillip (Elsevier Science BV, 2006)
The adsorption of polymers is typically characterised by segments of adsorbed "trains" and unadsorbed "loops" and "tails". Attenuated total reflectance infrared spectroscopy is thus an ideal means of studying this process in situ. In this study the adsorption of long chain polyacrylates onto hematite at pH 2 and 13 has been examined using a single bounce Horizontal-ATR cell. The crucial parameters that affect surface adsorbed densities obtained by this method are the depth of penetration and effective path length of the evanescent wave, and the infrared absorbtivities of the free and bound polyacrylate. The former require a detailed knowledge of the optical properties of the interface (refractive indices, incidence angles and polarisation fraction) whilst the latter can only be approximated, as it is not possible to measure the infrared absorptivity, nor the refractive index, of adsorbed polyacrylate independently. The results obtained show that only ~2-10% of the polymer chain is adsorbed, thereby confirming the "loops, tails and trains" mode of adsorption, and that higher molecular weight polyacrylates adsorb with a lower fraction of adsorbed segments.